2009
DOI: 10.1037/a0013340
|View full text |Cite
|
Sign up to set email alerts
|

Incentive contrast in domestic dogs (Canis familiaris).

Abstract: Dogs (Canis familiaris) trained to receive a preferred food (dry beef liver) from an experimenter learned to maintain a longer gaze on the experimenter than dogs receiving a less preferred food (dog pellets). Dogs downshifted from dry liver to pellets rejected food more frequently than nonshifted controls. Gaze duration also decreased in downshifted dogs below the level of a group always reinforced with pellets. In addition, downshifted dogs tended to move away from the experimenter, adopting a lying down post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
4
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 41 publications
5
68
4
1
Order By: Relevance
“…The results of this study provide further insight on the complex factors influencing and modulating dog-human interspecific communication, confirming that gazing behaviour in dogs is affected by environmental and life experiences, as has been shown in the literature (Barrera et al, 2011;Bentosela et al, 2009Bentosela et al, , 2008Marshall-Pescini et al, 2009;Passalacqua et al, 2011;Udell and Wynne, 2010). They indicate that specific training regimes aimed at promoting cooperation on a specific task that provide many learning opportunities might further enhance this ability in dogs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study provide further insight on the complex factors influencing and modulating dog-human interspecific communication, confirming that gazing behaviour in dogs is affected by environmental and life experiences, as has been shown in the literature (Barrera et al, 2011;Bentosela et al, 2009Bentosela et al, , 2008Marshall-Pescini et al, 2009;Passalacqua et al, 2011;Udell and Wynne, 2010). They indicate that specific training regimes aimed at promoting cooperation on a specific task that provide many learning opportunities might further enhance this ability in dogs.…”
Section: Discussionsupporting
confidence: 83%
“…Some authors, however, have underlined the importance of the domestication process attributing the domestic dog's sensitivity to human social cues to an human-like social cognition selected during domestication, considering such dog abilities neither simply inherited from wolves nor the result of ontogeny (Hare and Tomasello, 2005;Hare et al, 2010Hare et al, , 2002. Within an approach to socio-cognitive skills in dogs, which demonstrate the importance of selection (natural and artificial) and individual ontogenetic experiences (Miklósi and Topál, 2013;Udell et al, 2010b), a number of studies have assessed the role of learning, living conditions and the quality of the dog-human relationship in shaping the behaviour of dogs in different contexts, such as problem-solving tasks (e.g., Barrera et al, 2011;Bentosela et al, 2009Bentosela et al, , 2008Cunningham and Ramos, 2013;Horn et al, 2013;Marshall-Pescini et al, 2009, 2008Passalacqua et al, 2013;Range et al, 2009;Topál et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Learning plays an important role in the looking behaviour of dogs, and it has been clearly shown that reinforcement contingencies shape gazing towards humans (Bentosela et al 2008(Bentosela et al , 2009Horn et al 2009;Jakovcevic et al 2010;Barrera et al 2011;Protopopova et al 2012). For example, using a test situation comparable to that used in the current study, in which food was visible but out of the dogs' reach, Bentosela et al (2008) showed that gaze duration towards an experimenter's face significantly increased with just three reinforcement trials, and also quickly diminished when it was no longer reinforced.…”
Section: Discussionmentioning
confidence: 69%
“…Comparative work using animals to study reward processing has been valuable in the search for factors that mediate decision-making and choice behavior (Watanabe et al, 2001; Wikenheiser et al, 2013). Relative reward effects are pervasive in the animal kingdom (Bentosela et al, 2009; Wiegmann and Smith, 2009; Cromwell et al, 2005; Flaherty, 1996) and can be thought of as fundamental mechanisms that guide action in choice situations. Further analysis of the processes could lead to a better understanding for general mechanisms involved in reward valuation in diverse behavioral paradigms.…”
Section: Discussionmentioning
confidence: 99%